Immunogenicity and safety of Advax™, a novel polysaccharide adjuvant based on delta inulin, when formulated with hepatitis B surface antigen: A randomized controlled Phase 1 study - Gordon, David; Kelley, Peter; Heinzel, Susanne; Cooper, Peter; Petrovsky, Nikolai (Vaccine, 2014)
•Phase 1 first-in-man study of HBV vaccine based on Advax, a novel delta inulin-based adjuvant.•Advax enhanced both humoral and cellular immune responses to HBsAg.•Advax was safe and well tolerated in human subjects. There is a need for additional safe and effective human vaccine adjuvants. Advax™ is a novel adjuvant produced from semi-crystalline particles of delta inulin. In animal studies Advax enhanced humoral and cellular immunity to hepatitis B surface antigen (HBsAg) without inducing local or systemic reactogenicity. This first-in-man Phase 1 clinical trial tested the safety and tolerability of three intramuscular doses of HBsAg formulated with Advax in a group of healthy adult subjects. Advax was well tolerated with injection site pain scores not significantly different to subjects receiving HBsAg alone and no adverse events were reported in subjects that received Advax. Seroprotection and HBsAb geometric mean titers (GMT) after three immunizations were higher in the Advax 5mg (seroprotection 5/6, 83.3%, GMT 40.7, 95% CI 11.9–139.1) and 10mg (seroprotection 4/5, 80%, GMT 51.6, 95% CI 10.0–266.2) groups versus HBsAg alone (seroprotection 1/5, 20%, GMT 4.1, 95% CI 1.3–12.8). Similarly the proportion of subjects with positive CD4 T-cell responses to HBsAg was higher in the Advax 5mg (4/6, 67%) and Advax 10mg (4/5, 80%) groups versus HBsAg alone (1/5, 20%). These results confirm the safety, tolerability and immunogenicity of Advax adjuvant observed in preclinical studies. Advax may represent a suitable replacement for alum adjuvants in prophylactic human vaccines subject to confirmation of current results in larger studies. Australia and New Zealand Clinical Trial Registry: ACTRN12607000598482.